A Study on the Professional Development of Newly inducted Teachers through Teachers’ Talk and Narratives - Jain, Manju (THE PRIMARY TEACHER, 2010)
The pre-service and in-service teacher education programmes should be considered as inseparable components of any teacher preparation programme and viewed in totality in the context of schooling of children in variety of situations. These programmes are not an end for developing professional competency among teachers rather teacher preparation is a continuous life long learning process. This is also viewed as a two-way mutual exercise as teachers and trainers both learn from each other.